ANALISIS STUDI KELAYAKAN BISNIS PADA PENGEMBANGAN UMKM USAHA TAHU DAN TEMPE KARYA MANDIRI DITINJAU DARI ASPEK PRODUKSI, ASPEK PEMASARAN DAN ASPEK KEUANGAN - Siti Rahmadani; Makmur (Program Studi Manajemen Universitas Pasir Pengaraian, 2019)
This study aims to determine the business feasibility of Karya Mandiri Tofu and Tempe Business, to determine the feasibility of the non-financial aspects and the feasibility of the financial aspects. Feasibility analysis uses analysis of non-financial aspects, namely aspects of production and marketing aspects. Meanwhile, the analysis tools used for the financial aspect use Payback Period (PP) analysis, Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI), to determine whether a business is feasible or not. The results showed that Karya Mandiri Tofu and Tempe Business from the aspect of business production was declared feasible, because the strategic location of the business was easy to reach by consumers, the technology used was modern, and the production process was easy. The marketing aspect is feasible, with high quality products, because the raw materials are imported, the price is affordable, so that all people can buy it, the distribution is quite wide, and the promotions the owner gives are enough to make consumers know the products they sell. And the results of the analysis from the financial aspect show that the Tofu and Tempe Business is said to be feasible to run with a project life of 10 years at a discount rate of 10%. The analysis of the eligibility criteria resulted in a Payback Period (PP) for 8 months and 7 weeks, a Net Present Value (NPV) of IDR 137,689,184, a Profitability Index (PI) of 1.14% and an Internal Rate of Return (IRR) of 32% .